2020
DOI: 10.1177/0886109920906782
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing Barriers to Help-Seeking After Sexual Violence: A Critical Feminist Study With Latinx College Women

Abstract: This article is a critical feminist study focusing on illustrating how college students who identify as Latinx and women perceive barriers to help-seeking should they experience sexual violence. With this study, we address a gap in the research on help-seeking after sexual assault. The majority of research on this topic focuses on the experiences of European American women and is based on survey data. This study focuses on the perceptions and experiences of Latinx women attending a large, state institution. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Second, some traditional aspects of Catholic, Hispanic/Latinx cultures may cast women who have been sexually abused as impure or unvirtuous (Fontes, 1993), while simultaneously upholding Marianismo (i.e., a notion that women are spiritually stronger and have more of an ability to withstand pain than men; Comas-Diaz, 1995). Furthermore, a strong emphasis on upholding family pride among some Latinx individuals may prevent disclosure and help seeking behaviors, which could prolong feelings of guilt and shame following an abusive experience (Christensen et al, 2021). Finally, fatalism, or the idea that anything that happens is a function of God's will, is another cultural viewpoint that might lead an individual to interpret a traumatic experience as a punishment from God (Comas-Diaz, 1995).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Second, some traditional aspects of Catholic, Hispanic/Latinx cultures may cast women who have been sexually abused as impure or unvirtuous (Fontes, 1993), while simultaneously upholding Marianismo (i.e., a notion that women are spiritually stronger and have more of an ability to withstand pain than men; Comas-Diaz, 1995). Furthermore, a strong emphasis on upholding family pride among some Latinx individuals may prevent disclosure and help seeking behaviors, which could prolong feelings of guilt and shame following an abusive experience (Christensen et al, 2021). Finally, fatalism, or the idea that anything that happens is a function of God's will, is another cultural viewpoint that might lead an individual to interpret a traumatic experience as a punishment from God (Comas-Diaz, 1995).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In early Spring 2015, Dr. Christensen worked with their home university to implement a comprehensive sexual assault campus climate project which included a survey, focus group interviews, and a photovoice project (Christensen et al, 2015(Christensen et al, , 2020Yilmazli Trout et al, 2019). The climate survey results showed that approximately 70% of students had experienced at least one form of sexual harassment during their time at the university, and 25% of students had experienced seven or more forms of sexual harassment.…”
Section: Illustrative Case Study: Transforming Campus Rape Culturementioning
confidence: 99%
“…The first author designed a course for Masters of Social Work (MSW) students that used photovoice as a pedagogical tool for teaching specialized community practice (see Christensen et al, 2018Christensen et al, , 2020Yilmazli Trout et al, 2019). The first author taught three sections of this course, and each section implemented a separate photovoice project (two sections in Spring 2017 and one section in Fall 2017).…”
Section: Illustrative Case Study: Transforming Campus Rape Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This is a function of subjective norms, which are the beliefs or perceptions that significant others in society approve or disapprove of the behavior of an individual, and thus the behavior is regulated accordingly (Brouwer et al, 2009). Many studies have demonstrated that stigma is negatively associated with the intention to seek help regarding SE (e.g., Christensen et al, 2021; Kennedy & Prock, 2018; MacGinley et al, 2019; Olamide et al, 2012). One study in Nigeria found that 91.5% of female university students who were survivors of date rape never sought medical help, legal redress, or counselling services, and one of the reasons given was the fear of social stigmatization (Olamide et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%